Growth, yield and physiological activity of differently drip-irrigated vegetable cowpea (Vigna unguiculata) - LATA, KUMARI; YADAV, P K; RAM, H; KUMAWAT, PRIYANKA; VERMA, MANJU (The Indian Journal of Agricultural Sciences, 2024)
A study was carried during rainy (kharif) seasons of 2019 and 2020 at College of Agriculture (Swami Keshwanand Rajasthan Agriculture University, Bikaner, Rajasthan), Bikaner, Rajasthan to determine the best irrigation level along with suitable cowpea [Vigna unguiculata (L.) Walp] variety for a hot-arid region where water is a very limited resource. The experiment was conducted in a split-plot design (SPD), consisted of 4 treatments of irrigation, viz. T1, 40% PE; T2, 60% PE; T3, 80% PE; and T4, 100% PE with 4 cowpea varieties, viz. Kashi Kanchan; Kashi Nidhi; Pusa Sukomal; and Swarna Mukut, replicated thrice. Irrigation at 100% PE was found superior for number of primary branches, no. of pods/plant, net photosynthesis rate and carboxylation efficiency over the irrigation treatment 60% PE and 40% PE while statistically at par with 80% PE irrigation level. The days taken to first flower appearance were recorded minimum with 40% PE irrigation level. Irrigation at 80% PE exhibited maximum number of pickings, pod diameter, average pod weight, yield and water-use efficiency (WUE). Maximum plant height, number of primary branches and nodules/plant were recorded with Kashi Nidhi. Minimum days taken to flower initiation, maximum number of pickings, highest pod diameter, maximum number of pods/plant, average pod weight (g) and yield (q/ ha) were recorded by Swarna Mukut. Significantly higher net photosynthesis and carboxylation efficiency at pod formation were recorded with Swarna Mukut over the varieties Kashi Kanchan and Pusa Sukomal. Swarna Mukut exhibited significantly higher WUE (24.11 kg/ha mm) over Kashi Kanchan and Pusa Sukomal.